Micellization and Dissociation Behaviour of Zinc Stearate in Methanol-p-Xylene Mixtures by Conductance Measurements - Sonawane, G.H.; Patil, B.B.; Patil, H.A.; Shrivastava, V.S. (Asian Journal of Chemistry, 2016)
The critical micellar concentration of zinc stearate in a mixtures of methanol-p-xylene of varying compositions was determined at different temperatures (308.15, 313.15, 318.15, 323.15 K) by conductance measurement. The value of CMC increases with increase in temperature. The dissociation constant, degree of dissociation and limiting molar conductance were evaluated from conductivity measurements. The results show that this soap behaves as weak electrolyte in dilute solutions and the micellization process was dominant over the dissociation process.